The C/EBPβ LIP isoform rescues loss of C/EBPβ function in the mouse - Valérie Bégay (Nature Portfolio, 2018)
Abstract The transcription factor C/EBPβ regulates hematopoiesis, bone, liver, fat, and skin homeostasis, and female reproduction. C/EBPβ protein expression from its single transcript occurs by alternative in-frame translation initiation at consecutive start sites to generate three isoforms, two long (LAP*, LAP) and one truncated (LIP), with the same C-terminal bZip dimerization domain. The long C/EBPβ isoforms are considered gene activators, whereas the LIP isoform reportedly acts as a dominant-negative repressor. Here, we tested the putative repressor functions of the C/EBPβ LIP isoform in mice by comparing monoallelic WT or LIP knockin mice with Cebpb knockout mice, in combination with monoallelic Cebpa mice. The C/EBPβ LIP isoform was sufficient to function in coordination with C/EBPα in murine development, adipose tissue and sebocyte differentiation, and female fertility. Thus, the C/EBPβ LIP isoform likely has more physiological functions than its currently known role as a dominant-negative inhibitor, which are more complex than anticipated.